British orientalisms, 1759-1835 - Watt, James (Cambridge studies in Romanticism., 2019)
"In 1761 Richard Owen Cambridge published An Account of the War in India, telling the story of a decade of conflict between British and French forces in the south of the sub-continent. While this work says nothing about the 1757 battle of Plassey and the subsequent revolution that lead to the East India Company (hereafter EIC) gaining sovereign power in Bengal, it testifies to 'the great reputation which the nation, and so many individuals have acquired in the East-Indies'. Cambridge suggested that those, like him, without first-hand experience of India might already be primed to receive news of Britons' fantastic exploits there because of the 'Eastern' fictions to which they were accustomed: 'It will not appear strange that the generality of the world, through the habits of reading novels, and works of the imagination, should expect from an history of the East (... the scene of most of their ideal stories) a tale of adventures full of wonder and novelty, and nearly bordering upon romance'"--